Indonesia IDENTIFIKASI PERCEPATAN TANAH MAKSIMUM MENGGUNAKAN METODE MIKROTREMOR DI KOTA PADANG - Illona giovanni, Vannessa; Pujiastuti, Dwi; Pohan, Ahmad Fauzi (Universitas Andalas, 2025)
The position of Padang City on the coast and close to the subduction zone makes it very vulnerable to the impact of earthquakes, therefore mitigation efforts against potential disasters are very important to reduce the risk of such events. This study was conducted to map ground acceleration using the microtremor method as one of the efforts in earthquake disaster mitigation. The calculation of the maximum ground acceleration (PGA) value uses dominant frequency data (f0), amplification factor (A0 ) and soil vulnerability (kg) as input data obtained from microtremor data analysis using the Horizontal to vertical spectral ratio (HVSR) method. The microtremor data processed were 33 measurement points in 11 sub-districts in Padang City with a distance between points of 1-5 km. The dominant frequency, amplification, vulnerability and maximum ground acceleration values were then mapped to determine areas prone to earthquake disasters. Areas of Padang City with a high level of vulnerability can be seen in Bungus Teluk Kabung District and Padang Barat District.